Radiosynthesis and preclinical evaluation of [11C]Cimbi‐701 – Towards the imaging of cerebral 5‐HT7 receptors. (6th January 2020) - L 'Estrade, Elina T.; Shalgunov, Vladimir; Edgar, Fraser G.; Strebl‐Bantillo, Martin G.; Xiong, Mengfei; Crestey, François; Neelamegam, Ramesh; Dyssegaard, Agnete; Lehel, Szabolcs; Erlandsson, Maria; Ohlsson, Tomas; Hooker, Jacob M.; et al.
Abstract : The serotonin 7 (5‐HT7 ) receptor is suggested to be involved in a broad variety of CNS disorders, but very few in vivo tools exist to study this important target. Molecular imaging with positron emission tomography (PET) would enable an in vivo characterization of the 5‐HT7 receptor. However, no clinical PET radiotracer exists for this receptor, and thus we aimed to develop such a tracer. In this study, we present the preclinical evaluation of [ 11 C]Cimbi‐701. Cimbi‐701 was synthesized in a one‐step procedure starting from SB‐269970. Its selectivity profile was determined using an academic screening platform (NIMH Psychoactive Drug Screening Program). Successful radiolabeling of [ 11 C]Cimbi‐701 and subsequent in vivo evaluation was conducted in rats, pigs and baboon. In vivo specificity was investigated by 5‐HT7 and σ receptor blocking studies. P‐gp efflux transporter dependency was investigated using elacridar. [ 11 C]Cimbi‐701 could successfully be synthesized. Selectivity profiling revealed high affinity for the 5‐HT7 (Ki = 18 nM), σ‐1 (Ki = 9.2 nM) and σ‐2 (Ki = 1.6 nM) receptors. In rats, [ 11 C]Cimbi‐701 acted as a strong P‐gp substrate. After P‐gp inhibition, rat brain uptake could specifically be blocked by 5‐HT7 and σ receptor ligands. In pig, high brain uptake and specific 5‐HT7 and σ‐receptor binding was found for [ 11 C]Cimbi‐701 without P‐gp inhibition. Finally, low brain uptake was found in baboons. Both the specific σ‐receptor binding and the low brain uptake of [ 11 C]Cimbi‐701 displayed in baboon discouraged further translation to humans. Instead, we suggest exploration of this structural class as results indicate that selective 5‐HT7 receptor imaging might be possible when more selective non‐P‐gp substrates are identified. Abstract : In this study, we present in vitro characterization, radiosynthesis, and in vivo evaluation of [ 11 C]Cimbi‐701 in three different species. Selectivity profiling revealed that Cimbi‐701 binds with high affinity to 5‐HT7 and σ receptors. In vivo PET experiments confirmed that [ 11 C]Cimbi‐701 binds to both targets in the rat and pig brain. Low brain uptake was found in the baboon.